Sulfate attack, freeze-thaw and high-temperature performances by evaluation of colemanite waste as binding material and aggregate in green geopolymer production - Basturk, Tugce Beyza; Yilmaz, Arin; Aygormez, Yurdakul (ELSEVIER, 2025)
To turn the construction industry into a green application phase, alternatively, cementitious source materials have been partially or completely replaced by waste materials and industrial byproducts. With this situation, boron minerals and products have a wide usage area and are increasing daily. The most common of the boron minerals is colemanite. In this study, in addition to using blast furnace slag (S) and fly ash (FA) as source materials in geopolymer mortar production, the mechanical and durability performances of geopolymer mortars by evaluating colemanite waste (CW) instead of both source material and aggregate were compared with 10 different series cured at room temperature. Mechanical properties were investigated on the 7th, 28th, and 90th days. For the durability study, a high-temperature test (300, 600, and 900 degrees C), freeze-thaw test (15 cycles), and sulfate solution attack test (10% magnesium sulfate (MgSO4) and sodium sulfate (Na2SO4)) were performed. Also, SEM, XRD, and TGA-DTA analyses were used to examine the situation before and after the durability tests. Substitution of colemanite waste up to 10% as a source material allowed it to show a strength increase. The highest compressive strength result on the 90th day was 39.06 MPa in the series where it was replaced with 5% fly ash. In the case of using colemanite as an aggregate, results close to the control sample were obtained. In the high temperature and freeze-thaw test, the colemanite waste formed a protective layer and provided better results in the series in which it was replaced by slag and used as an aggregate.
Keywords: Colemanite waste; Slag; Fly ash; Geopolymer; FLY-ASH; COMPRESSIVE STRENGTH; PORTLAND-CEMENT; MECHANICAL-PROPERTIES; SILICA FUME; CONCRETE; METAKAOLIN; BEHAVIOR; DURABILITY; RESISTANCE; Chemistry; Science & Technology - Other Topics; Environmental Sciences & Ecology